1050. Breath Sample Collection from Individuals Infected with SARS-CoV-2: Biosafety Methodology. (15th December 2022) - Lopez, Marcela; Lopez, Marcela; Stainton, Emma; Chun, Leanne X; Tam, Grace K; Thiessen, Rosita; Carrington, Yuan J; Idziak, Luke; Hannon, Ami M; Duanmu, Youyou; Trounce, Milana Boukhman; Altamirano, Jonathan; et al.
Abstract: Background: Breath samples collected from patients infected with respiratory viruses are necessary for viral detection using breath analyzer devices. Given the highly transmissible nature of many of these illnesses, sample collection requires a multi-layered approach to ensure the safety of the research staff responsible for obtaining and transporting these samples. Our team established a protocol to minimize exposure to and transmission of COVID-19 when collecting breath samples. Methods: We collected breath samples from 64 participants, of which 31 (48.4%) were positive for SARS-CoV-2 at the time of their visit. Before we started sample collection, biosafety inspection was conducted. We used a five-pronged approach to enhance safety and minimize transmission. First, we collected specimens in an outdoor space while the patients were seated in their vehicles. Second, we used a disposable mouthpiece and a one-way valve to fill a 1L TEDLAR bag. Third, patients were instructed to close the valve tightly before returning it to the staff. Fourth, we placed the bag in secondary containers which were placed in tertiary containers to minimize any contact with aerosols in the TEDLAR bag. In the last step, we placed a portable HEPA filter near the indoor sample processing unit to minimize exposure and air contamination with the samples. Study staff donned all forms of necessary personal protective equipment, including gloves, gowns, N95 respirators, and protective eyewear, during sample collection and transportation. Results: A total of 64 breath samples were collected from 64 adult participants from February to March 2022. A total of 30 participants (46.9%) were within 7 days of their initial diagnosis. All participants were able to successfully collect samples without additional resources or attempts. All samples were able to be transported successfully into the lab. No staff contracted COVID-19 during the study period. Conclusion: Layered safety measures, including protective equipment, physical barriers, and well-ventilated environments mitigated the risks associated with breath sample collections from infected participants. Disclosures: Yvonne A. Maldonado, MD, Pfizer: Grant/Research Support|Pfizer: Member, DSMB, Pfizer Meningococcal Vaccine clinical trial.